Chemical reaction simulator on quantum computers by first quantization—Basic treatment: Theoretical - Tatsuya Tomaru; Hideo Takahashi; Toshiyuki Hirano; Saisei Tahara; Fumitoshi Sato (AIP Advances)
Quantum computers can potentially simulate quantum-mechanical phenomena, so chemical reactions are a potential application of them. In particular, the time evolution of the wavefunctions should be simulated because chemical reactions are accompanied by structural changes. In this study, to pave the way to achieving such wavefunction simulations, we decompose chemical reactions into their main parts and comprehensively show the minimum essential circuits for simulating each part. An antisymmetrized initial state is constructed using ancillae. Chemical reactions should be simulated in two different ways, where the difference is whether the ancillae are released or not. When they are released, the whole electronic system is simulated. When they are not released, orbital information is obtained. These ways are hence complementary.